John Gray: In Conversation. - Callahan, Gene (Modern Age)
This article is an interview with John Gray, a professor of European thought, discussing a range of topics including Israel's war, Michael Oakeshott, C.S. Lewis, and more. Gray's latest book, "The New Leviathans: Thoughts After Liberalism," explores the challenges of the 21st century through the lens of Thomas Hobbes's philosophy. The interview touches on recent events in Gaza and the demonstrations in support of Palestine, with Gray expressing his views on the situation and highlighting the underlying anti-Semitism in some progressive ideologies. The text also explores the concept of intellectual freedom and the repression of intellectual freedom in the 20th century, as well as the issue of language and its role in avoiding real human issues. The conversation challenges the idea that Darwinism necessarily leads to progressivism or liberalism and emphasizes the importance of recognizing the complexity of human nature. C.S. Lewis and his works are also referenced in the conversation.